Analisa Rekonfigurasi Pada Feeder Sibuak Untuk Mengurangi Rugi-Rugi Daya Dan Drop Tegangan Dengan Menggunakan Etap 12.6.0 - Torang Harison; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The end of Sibuak line feeder facing a voltage drop phenomena. This phenomena is contributed by the length of the transmission line, as well as the distribution line. This paper purposes a reconfiguration of Sibuak feeder in order to reduce amount of power losses and the drop voltage. The design of reconfiguation Sibuak feeder refers to PLN standard (SPLN 1,1978).This reconfiguration uses LBS status updating approach which is triggered from Normally Close (NC) into Normally Open (NO) or in the refers condition. Beside that, it is required load transfer from Sibuak Feedr in to Cadika Feeder. The result of ETAP 12.6.0 software indicates that the reconfigured Sibuak Feeder able to achieve lowest voltage on 18,162 kV with power losses shows 1,652 and 1,186 MVAR respectively..Keywords : power losses, voltage drop, feeder of sibuak, ETAP 12.6.0